Future Trand, Prospects and Challanges of Digital Media Reportage in Nigeria - Ivwighren, Hannah; Oghiagbepha, Oghenekevwe (Universitas Negeri Surabaya, 2024)
The trend in the use of digital media for reportage in Nigeria is dynamic due to the impact of technology, growth in internet usage, and the adoption of social media. This paper aims to identify the future trends of digital media reportage in Nigeria by assessing the latest trends in digital media. Prospect was also assessed and challenges were discussed to provide a balanced view of the discussion. In light of the rationale grounded on media ecology theory, the study was conducted with a survey design approach accompanied by key informant interview analysis. The target population was 2936 postgraduate students of Delta State University, Abraka. The sample was 293 indicating 10% of the target population. The tool employed for data collection was a structured questionnaire containing a Likert scale and a purposive sampling technique. Consequently, the use of descriptive statistical analysis facilitated a summary of demographic information, media consumption and exposure toward digital media in Nigeria. STATA 0.13 statistical app aided the analysis process to assess the mean and standard deviation values. The study findings reveal that there is a trend towards consuming more engaging content, particularly through the use of A. I and A.R. Digital media have the potential to increase chances of inclusion, share information, and increase citizen journalism. However, challenges have not been completely done away with, like misinformation, and lapsed regulatory hurdles. Based on the findings of the study, it can be asserted that there is great potential for the development of digital media reportage for effective civic engagement, representation of pluralism, and socio-economic advancement in Nigeria. As a result, it is recommended to establish effective regulation by the positioned bodies and stakeholders to fight against false information, personal data protection, and investigative journalism standards to protect the public’s interests.